A case of Murray Valley encephalitis in a 2‐year‐old Australian Stock Horse in south‐east Queensland. Issue 3 (March 2015) - Barton, AJ; Prow, NA; Hall, RA; Kidd, L; Bielefeldt‐Ohmann, H
<x xml:space="preserve">Abstract</x> Case report This report summarises the findings from a case of naturally‐occurring Murray Valley encephalitis in a 2‐year‐old filly presenting with acute onset of depression and weakness. Serum samples tested at the onset of clinical signs were negative for Hendra and Kunjin virus antibodies, but positive for Murray Valley encephalitis virus (MVEV) using IgM‐capture ELISA (1 : 300 dilution). A virus neutralisation assay performed 4 weeks later confirmed a titre of 1 : 160. Sera collected in the weeks preceding neurological signs returned a negative titre for MVEV 2 weeks prior followed by a titre of 1:80 in the week prior to illness. Serological surveillance conducted on 67 co‐located horses returned a positive titre of 1 : 20 in one in‐contact horse. There was no history of clinical disease in that horse. At 3 months after the onset of clinical signs in the index case, the filly continued to show mild facial paresis and hypermetria; the owners elected euthanasia and gave permission for necropsy. Histopathological analysis of the brain showed a mild meningoencephalitis. Conclusion The progression of a naturally‐occurring MVEV infection in a horse has been documented in this case.